2D porous carbon nanosheets derived from turnip: Preparation, characterization and its electrochemical performance. (March 2023) - Jiang, Tiantian; Nasser, Ramzi; Wang, Xiaolu; Trabelsi, Amira Ben Gouider; Alkallas, Fatemah Homoud; Elhouichet, Habib; Song, Ji-Ming
Abstract: Biomass-based porous carbon materials have appeal due to their low cost, abundance and sustainability. In this report, a novel kind of heteroatom (N, S) co-doped 2D porous activated carbon using turnip as biomass has been prepared with subsequent non-toxic dual activators. At optimized activation temperature, the activated carbon from turnip-derived using KCl/NaCl (ACTKNa) as activators shows excellent surface area of 1938 m 2 ·g −1 with micro-mesopores distributions. Importantly, ACTKNa as electrode materials for supercapacitors exhibits a superb capacitance value of 570 F·g −1 (0.5 A·g −1 ) and retains high stability. Interestingly, a symmetric ACTKNa//ACTKNa device can work in the potential window (0–1.5 V) under neutral Na2 SO4 solution. Among them, the symmetric device delivers specific energy value 47.5 Wh·kg −1 at specific power of 372 W·kg −1 with outstanding rate capability of 86 % after 20, 000 cycles. This work opens the way to enhance the specific energy value by increasing the potential window using neutral electrolyte. Graphical abstract: We highlight an environmentally friendly strategy to successfully prepare N, S co-doped turnip-derived porous activated carbons using neutral, non-toxic and non-corrosive dual activators NaCl/KCl. The obtained carbon material had large surface area (1938 m 2 ·g −1 ), and exhibited a superior specific capacitance (570 F·g −1 at 0.5 A·g −1 ) and retains high stability as electrode material of supercapacitor. The symmetric ACTKNa//ACTKNa device with the potential window (0–1.5 V) could deliver excellent specific energy value 47.5 Wh·kg −1 at specific power of 372 W·kg −1 . Unlabelled Image Highlights: N/S co-doped 2D porous activated carbon were prepared from turnip biomass. Non-toxic and non-corrosive neutral double salts NaCl/KCl were used as activator. The porous carbon exhibited high specific capacitance of 570 F·g −1 at 0.5 A·g −1 . The device delivers specific energy of 47.5 Wh·kg −1 at specific power of 372 W·kg −1 .